PROTOTYPE OF ELECTROCARDIOGRAM USING ESP32 - Carrasqueira, Rafael; Mendes, Oswaldo Lazaro; Carrasqueira, Arthur (Revista Interface Tecnológica, 2022)
Caring about the pet's health is important to ensure comfort and increase the longevity of the pet, in this way, monitoring the heart rate variability of your pet will allow a greater longevity of the pet. The objective of this work is to approach the prototyping of an electrocardiogram using an ESP32 microcontroller module for analyzing and monitoring the heart rate of pet dogs, presenting the development of the prototype and its practical application. As a basis for this project, bibliographic research was used based on books, internet articles for the development of the prototype. As a result, we have a low-cost meter prototype that can be easily used. Finally, the benefits and the possibility of applying the ECG system are shown in order to bring a better quality of life for pets
Keywords: ECG; Electrocardiogram; Cardiac; Dogs; ESP32